The Emergence of Extensively Drug-Resistant Tuberculosis (TB): TB/HIV Coinfection, Multidrug-Resistant TB and the Resulting Public Health Threat from Extensively Drug-Resistant TB, Globally and in Canada - Paul E Alexander; Prithwish De (Canadian Journal of Infectious Diseases and Medical Microbiology)
Resistance to anti-tuberculosis (TB) drugs continues to present a major challenge to global public health. Resistance usually develops due to inadequate TB management, including improper use of medications, improper treatment regimens and failure to complete the treatment course. This may be due to an erratic supply or a lack of access to treatment, as well as to patient noncompliance. However, the emergence and transmission of drug-resistant TB, including the recently detected extensively drug resistant TB (XDR-TB), is driven, in part, by the synergistic relationship between TB and HIV (TB/HIV coinfection). There is evidence that persons infected with HIV are more likely to experience XDR-TB. XDR-TB is virtually untreatable with available TB medications. XDR-TB presents a grave global public health threat, particularly in high HIV prevalence settings. The present commentary discusses the current status of XDR-TB and draws attention to the urgency in addressing this problem, for both the global and Canadian public health networks. XDR-TB and the apparent XDR-TB and HIV association warrants further study.